PENGARUH TINGKAT PENGETAHUAN TENTANG KESEHATAN REPRODUKSI TERHADAP PERILAKU SEKSUAL SISWA DALAM BERPACARAN (Studi Kasus Di SMK Kesehatan Mulia Husada Kabupaten Sumenep) - Dian Ika Puspitasari; Zakiyah Yasin; Ike Yulianti (Fakultas Ilmu Kesehatan, 2013)
With existence of information current through media a period of good in the form of magazine, newspaper, tabloid and also electronic media like radio, television, and computer can influence adolescent to do things which per me risk for example braiding the relation of sexual external marries, liquor, narkoba which can result pregnancy is not wanted and other reproduction risk, also is infected sexual catching infection is including HIV/AIDS.Intention of this research is to know relation between level of knowledge about health of reproduction to sexual behaviour in having an affair by using design cross sectional. As population in this research is students SMK Kesehatan Mulia Husada Sumenep, Sub-Province Sumenep and its the sample is Students SMK Kesehatan Mulia Husada Sumenep, Sub-Province Sumenep which or medium of haves an affair with number of 71 and way of sampling with technique cluster random sampling and data is presented in the form of tables and analysed with rank spearman ( rho).Result of research of shows level of good knowledge 48 responders (68%) and unfavourable sexual behaviour 36 responders (51%), test result rank spearman ( rho) shows ρ = 0,021 < ά 0,05 refusing H0 so that inferential that there is medium relationship between health knowledges of reproduction with student sexual behaviour in having an affair.From result of research of shows that there is relation between level of knowledge of student with sexual behaviour, in consequence improvement of knowledge of student about education of sexual needs defended and improved.Keyword :Reproduction Health, Sexual behaviour, Student.